Modeling of Factors Affecting the Open Unemployment Rate in East Java - Haryanto, Albertus Eka Putra; Zulfadhli, Muhammad; Alimuddin, Ahmad Hilal (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
One of the challenges faced in achieving the Sustainable Development Goals (SDGs) in point eight is the high unemployment rate in several regions. East Java Province is one of the provinces with a relatively high Open Unemployment Rate (TPT) compared to the target set by the provincial government in 2021. In that year, East Java's TPT was recorded at 6.49%, exceeding the specified target of between 3.96% and 4.01%. In addition to the impact of the COVID-19 pandemic, several other factors are thought to have a significant influence on the East Java TPT. This study aims to model these factors using linear and nonparametric regression with a truncated spline approach to identify the best model. The data used in this study are secondary data from the Badan Pusat Statistika (BPS). The results showed that the best model based on the highest R² value and the lowest RMSE was nonparametric regression with a truncated spline. The variables of district/city minimum wage,Labor Force Participation Rate, and Human Development Index (HDI) have a significant effect on TPT in East Java, where this model is able to explain 91.51% of the variability in the model.